Clinical profile, associated risk factors and oral health-related quality of life in recurrent aphthous stomatitis: A cross-sectional study - Ashutosh Pandey (Bioinformation, 2026)
Recurrent aphthous stomatitis (RAS) is the most prevalent ulcerating condition of the mouth mucosa. Therefore, it is of interest to evaluate the clinical profile and distribution of RAS subtypes and determine risk factors which are associated with disease severity as well as its effect on oral health-related quality of life (OHRQoL). Psychological stress (adjusted OR = 3.42, 95%CI = 1.24-9.43, p = 0.018) and haematinic deficiency (adjusted OR = 2.96, 95%CI = 1.02-8.59, p = 0.046) were independently associated with moderate and severe RAS and their OHIP-14 scores showed a significant increase with increasing severity (Mild: 9.1 ą 4.2, Moderate: 16.8 ą 5.6, Severe: 24.3 ą 6.1; ANOVA p < 0.001). Thus, RAS in this population was mainly minor, predominantly occurred in young females with psychological stress. Moreover, haematinic deficiency and it is the independent factors predicting severity and poor OHRQoL.